Pedagogic and learning spaces of leadership development: A sectoral case study - Jivan, A.M.; Paile, M. (South African Journal of Higher Education, 2019)
This article develops the critical reviews of the leadership development terrain and argues for the necessity to consider and explore the pedagogic spaces of leadership development and its constitutive dynamics. It first synthesises the theoretical debates on pedagogic space by identifying five relevant themes and how pedagogic and learning spaces are differentiated. It locates itself within these debates, focusing on assemblage, embodiment and enactment. It then draws on a case study of the South African retail banking sector to suggest a sectoral analysis. The value and contribution of this is the attention to different levels of analysis and the theme of journeys. It allows for the consideration of, and deliberation on, expanding and opening up pedagogic and learning spaces.